Infant feeding and analgesia in labour: the evidence is accumulating - Jordan Sue (BMC, 2006)
Abstract The interesting and important paper by Torvaldsen and colleagues provides further circumstantial evidence of a positive association between intrapartum analgesia and feeding infant formula. Not all research supports this association. Before 'failure to breastfeed' can be adjudged an adverse effect of intrapartum analgesia, the research evidence needs to be considered in detail. Examination of the existing evidence against the Bradford-Hill criteria indicates that the evidence is not yet conclusive. However, the difficulties of obtaining funding and undertaking large trials to explore putative adverse drug reactions in pregnant women may mean that we shall never have conclusive evidence of harm. Therefore, reports of large cohort studies with regression models, as in the paper published today, assume a greater importance than in other areas of investigation. Meanwhile, women and their clinicians may feel that sufficient evidence has accumulated to justify offering extra support to establish breastfeeding if women have received high doses of analgesics in labour.